2020
DOI: 10.31557/apjcp.2020.21.4.975
|View full text |Cite
|
Sign up to set email alerts
|

Molecular miR-19a in Acute Myocardial Infarction: Novel Potential Indicators of Prognosis and Early Diagnosis

Abstract: Objective: Due to the increasing annual incidence rate of disability and mortality in patients with acute myocardial infarction (AMI), the need for an appropriate diagnostic tool has become a crucial urgent issue. An increase in biomarkers and protein levels in response to AMI can be used as a predictive biomarker with different sensitivities and specificities. This study aimed at investigating the role of miR-19a as a biomarker with acceptable sensitivity and specificity for early diagnosis of AMI. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The total RNA was extracted using the RNeasy Mini Kit (Qiagen). The complementary DNA (cDNA) of miRNA was obtained by the reverse transcription of miRNA using the miRNA First Strand cDNA Synthesis (Tailing Reaction) kit (B532453‐0020; Sangon Biotech) and that of mRNA by the reverse transcription of mRNA using the reverse transcription kit (RR047A; Takara Bio), respectively 9 . RT‐qPCR was performed on a Bio‐Rad instrument (10 021 337; Bio‐Rad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total RNA was extracted using the RNeasy Mini Kit (Qiagen). The complementary DNA (cDNA) of miRNA was obtained by the reverse transcription of miRNA using the miRNA First Strand cDNA Synthesis (Tailing Reaction) kit (B532453‐0020; Sangon Biotech) and that of mRNA by the reverse transcription of mRNA using the reverse transcription kit (RR047A; Takara Bio), respectively 9 . RT‐qPCR was performed on a Bio‐Rad instrument (10 021 337; Bio‐Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, other studies have illustrated the protective effect of Dex on the ischaemic or reperfusion injury of various organs including the heart and kidney 8 . On the other hand, recent studies have indicated the prognostic value of circulating miR‐19a and suggested it as a promising molecular target for early diagnosis and prognosis of acute myocardial infarction 9 . Though microRNAs (miRNAs), that is miR‐129‐5p 10 and miR‐29b, 11 have indicated being involved in the neuroprotective effect of Dex.…”
Section: Introductionmentioning
confidence: 99%
“…Some biomolecules can be accumulated into exosomes that are regularly released from the blood. The role of exosomes as a vesicle to secrete and store biological molecules is crucial [ 66 ]. Hence, MSC-secreted exosomes have been increasingly recognized as a multicomplex paracrine factor that carries different biomolecules, for instance, a series of uncoded miRNAs like miR-34a, miR-200b/c, miR-146a, and Let-7 which are classified via their interaction with proinflammatory mediators.…”
Section: Cell-based Therapies For Covid-19mentioning
confidence: 99%
“…Disability in patients is associated with the severity of the cardiac defect and reflected the degree of one or more cardiac artery stenosis or cardiac region ischemia. Each year, many reconstructive surgical procedures and invasive bypass surgery are performed to repair heart-tissue defects, traumatic cardiovascular injury, and congenital defect 55 . The standard care based on electrospun PCL for heart tissue reconstruction is responsible for restoration in injured myocardium cells, leading to increased blood supply in injured myocardium or local angiogenesis.…”
Section: Electrospun Pcl Nanofibers and Tissue Engineeringmentioning
confidence: 99%